Collaborative E-learning Methodologies: an Experience of Active Knowledge in ICT Classrooms - Simões, Dora (2012)
In the present study we highlight a specific environment that makes use of collaborative technological tools, like wikis and forums within an e-learning platform. Both of these approaches convey a lot of responsibility from the teacher to the students and the hoping, as backed up by the literature, is to promote deeper learning and reasoning skills at a higher level. The general goal of this paper is to contribute for the theoretical discussion on how active and collaborative experiences in ICT classrooms play a role on the construction of knowledge in HEIs. Based on the pointed outlines, we intend to: (1) understand how collaborative e-learning environments get students actively involved in the learning process;(2) perspective the role of collaborative tools at the level of group work and (3) find out how students assess their performance within a working group. Data was collected through questionnaires available on the e-learning platform Moodle. Descriptive statistical techniques were used to analyze quantitative data. Within the research questions proposed, the study, points towards some understanding of how a collaborative learning environment seems to get students actively involved in the learning process mainly if the tasks to be perform have an empirical component. The study also has shown that students seem to identify themselves with the need to be involved in simulations of their future professional activity, as well as with the need to regulate their own learning and to promote discussion not only between peers but also with the teacher.